High-Dose Intravenous Immunoglobulin in Skin Autoimmune Disease - Hoffmann, Jochen H. O.; Enk, Alexander H. (Frontiers in Immunology, 2019)
The immunomodulatory potential and low incidence of severe side effects of high-dose intravenous immunoglobulin (IVIg) treatment led to its successful application in a variety of dermatological autoimmune diseases over the last two decades. IVIg are usually administered at a dose of 2g per kg body weight distributed over two to five days every 4 weeks. They are most commonly used as a second or third line treatment in dermatological autoimmune disease (pemphigus vulgaris, pemphigus foliaceus, bullous pemphigoid, mucous membrane pemphigoid, epidermolysis bullosa acquisita, dermatomyositis, systemic vasculitis, and systemic lupus erythematosus). However, first line treatment may be warranted in special circumstances like concomitant malignancy, a foudroyant clinical course, and contraindications against alternative treatments. Furthermore, IVIg can be considered first line in scleromyxedema. Production of IVIg for medical use is strictly regulated to ensure a low risk of pathogen transmission and comparable quality of individual batches. More common side effects include nausea, headache, fatigue, and febrile infusion reactions. Serious side effects are rare and include thrombosis and embolism, pulmonary edema, renal failure, aseptic meningitis, and severe anaphylactic reactions. Regarding the mechanism of action, one can discriminate between functions of the Fcγ region, the F(ab)2 region and effects on a cellular level. These functions are not mutually exclusive and more than one pathway may contribute to the beneficial effects. Here, we present a historical background, details on manufacturing, hypotheses on the mechanisms of action, information on the clinical application in the above-mentioned conditions and a brief outlook on future directions of IVIg treatment in dermatology.